Intraoperative Neurophysiologic Monitoring for Prediction of Postoperative Neurological Improvement in a Child With Chiari Type I Malformation. Issue 7 (October 2017) - Kawasaki, Yukari; Uchida, Susumu; Onishi, Kouhei; Toyokuni, Masako; Okanari, Kazuo; Fujiki, Minoru
Abstract : Introduction: Although many surgical treatment strategies for Chiari malformation type I (CM-I) have been reported, the most appropriate surgical technique remains controversial. It is wholly ascribable to the complicacy of pathological condition in CM-I. Recently, intraoperative neurophysiologic monitoring (INM) is becoming prevalent in spinal surgery. Indeed, motor-evoked potentials (MEPs) monitoring and somatosensory-evoked potentials (SSEPs) monitoring are standard tools to minimize the risk of neurologic injury and postoperative deficits. The most recent study suggested that multimodality INM can be beneficial in foramen magnum decompression surgery for CM-I patients for surgical positioning and planning. Various authors have investigated the consistency of intraoperative evoked potential changes that might aid the surgeon to determine the appropriate extent of decompression required for an individual patient. Patient Description: The authors report the case of a 7-year-old boy who had the signs of medullary and cerebellar dysfunction, clumsy hands, and ataxic gait. He underwent a surgery of foramen magnum decompression with tonsillectomy and duraplasty for CM-I with cervicomedullary compression. His intraoperative MEPs improved (indicated increased-amplitude and shortened-latency) both after craniotomy and durotomy, whereas SSEPs improved only after durotomy. Those results were correlated well with a functional improvement that was apparent in the immediate postoperative hospitalization. Conclusions: The authors' data provides 1 possible interpretation of INM for safety aspect, but also which degree of decompression in each patient will require. The improvement in MEPs and SSEPs observed during decompression procedure may be a good indicator for the prediction of the clinical improvement seen postoperatively.